Numerical study of MWCNT enhanced PCM melting through a heated undulated wall in the latent heat storage unit. (1st January 2022) - Gupta, Anoop K.; Mishra, Garima; Singh, Shikha
Graphical abstract: Highlights: The undulated wall enhances the rate of melting of the PCM. Addition of MWCNT particles in the PCM increases the rate of melting. Melting time decreases with increasing values of α/λ. Results are identical for fixed values of α/λ. The sinusoidal heat flux provides minor improvement over uniform heat flux condition. Abstract: The use of phase change materials (PCMs) is an efficient passive technique for thermal energy management. However, its low thermal conductivity presents significant technological challenges. Several methods have thus been employed to improve the thermal performance of a latent heat thermal energy storage (LHTES) unit. Here, the melting and heat transfer characteristics for the multi-walled carbon nanotube (MWCNT) enhanced PCM (n-octadecane) inside a square duct with a vertical undulated wall has been examined. Extensive results on streamlines, temperature contours, rate of melting and energy storage, and the Nusselt number have been presented to delineate the influence of various pertinent parameters as: amplitude of undulations (0 ≤ α ≤ 0.002 m), wavelength of undulations (0.0025 ≤ λ ≤ 0.02 m) and volume fraction of MWCNT particles (0 ≤ ϕ ≤ 0.06). In addition, the results from two different heat flux conditions, namely, uniform and sinusoidal heat flux have also been compared. Overall, the complete melting time reduces drastically with an increase in the value of the amplitude to wavelength ratio (α/λ). This functional dependence has been presented in form of a simple predictive correlation. Also, an increase in the volume fraction of MWCNT particles in the PCM enhances the rate of melting. However, this enhancement is more significant for high values of α/λ.